Evaluating the Effects of Chemical Composition on Induction Heating Ability of Fe2O3-CaO-SiO2 Glass Ceramics - Y. Y. Wang; B. Li; Y. L. Yu; P. S. Tang (Advances in Materials Science and Engineering)
In order to investigate the relationship between induction heating ability of Fe2O3-CaO-SiO2 glass ceramics and chemical composition, a series of glass ceramic samples with different chemical compositions were prepared by the sol-gel method. The structural, textural, and magnetic properties of the samples were analyzed and correlated with the Fe2O3 content. This is the first time work of its kind that evaluates the relationships between induction heating ability and chemical composition of Fe2O3-CaO-SiO2 glass ceramics. The results showed that induction heating ability of Fe2O3-CaO-SiO2 glass ceramics increased gradually with increasing magnetite content. Also, the induction heating ability became considerably better when a small amount of phosphorus was introduced. This study thus reveals a methodology to control the induction heating ability of Fe2O3-CaO-SiO2 glass ceramics through modifying the chemical composition.